Taro Potato Sustainability Innovation : As an Alternative to Bioramah Rice Wrapping for Farmer Groups in Blitar Regency - Yuli Agustina; Evi Susanti; Fadia Zen; Muhammad Mujtaba Habibi (CV. Proaksara Global Transeduka, 2024)
This study explores the sustainability innovation of taro potato as an alternative to environmentally friendly rice wrapping, aimed at farmer groups in Blitar Regency. The research investigates the potential of taro potato, a locally abundant and underutilized resource, to replace traditional non-biodegradable materials used in rice wrapping. By introducing taro potato as a sustainable alternative, the study seeks to provide an eco-friendly solution that aligns with the growing demand for green practices in agriculture. The findings indicate that taro potato-based wrapping not only reduces environmental impact but also adds value to local agricultural products, thereby supporting the economic sustainability of farmer groups in Blitar Regency. This innovation has the potential to enhance environmental stewardship and promote sustainable agricultural practices within the community.